Factor analysis, reliability and validity of a measurement model for the intent of alcohol consumption among ecuadorian teenagers - Moreta-Herrera, Rodrigo (2020)
Objective. Confirm the bifactorial structure, reliability and validity of the Modelo de Medición de Intención al consumo de Alcohol (MMICA), in a sample of Ecuadorian adolescents. Method. Instrumental study with factor analysis, reliability and validity (construct and criterion) of the MMICA among risky and not risky consumers. The sample was 480 students (52.3% men), between 12 to 19 years (M= 14.8, SD= 1.5), from three different educational centres (67.9% public) of Ambato and Pelileo cities, Ecuador. Results. The bifactorial structure is confirmed with a variance explained of 72.1%, the adjustment data are adequate with X2= 39.9; p< .001; df= 26; X2/df=1.5; CFI= .98; TLI= .97; SRMR= .045; RMSEA=.048 [.011 - .077]. Reliability is high (ω=.90 for behavioural control and ω=, 84 for behavioural belief). This study confirms criterion validity between risky and not risky alcohol consumers. Conclusions. The MMICA is an adequate, reliable and valid test to assess intent of alcohol consumption among Ecuadorian adolescents. © Health and Addictions 2020